Efficacy of various multi-layers of orthodontic clear aligners: a simulated study. Issue 15 (31st October 2022) - Jia, Lurong; Wang, Chunjuan; Wang, Chao; Song, Jinlin; Fan, Yubo
Abstract: Background: In the invisible orthodontic treatment, composite thermoforming film materials have become the focus of orthodontic clear aligners. The orthodontic efficacy of clear aligners which consisted of multi-layers materials remains unclear. This study aims to evaluate the biomechanical effects of various multi-layers of clear aligners on en-mass retraction of maxillary anterior teeth. Methods: A patient-specific 3D non-linear finite element model numerical analysis was constructed to simulate the en-mass retraction of maxillary anterior teeth with clear aligner after extraction of the first premolars. Four kinds of multi-layers clear aligners with different proportion of film materials were simulated. The biomechanical responses of four different clear aligners on invisible orthodontics were calculated. The tooth displacement in all directions, the hydrostatic pressure of periodontal ligament, the orthodontic deformation of clear aligner, and the stress distribution of alveolar bone were compared and investigated. Results: In all experimental models, the maximum equivalent deformation of alveolar bone, the vector displacement of tooth and the compressive/tensile stress of periodontal ligament decreased with the increase of soft layer thickness. The elastic strain of clear aligners also decreased with the increase of the ratio of soft/hard layers. Conclusions: The multi-layers clear aligner is better than the single-layer clear aligner in tooth movement, stress distribution of periodontal ligament and mechanical loading of alveolar bone, especially when the ratio of soft layer to hard layer is more than 50%. Moreover, the side effects of the multi-layers clear aligner are significantly less than those of the single-layer one.